2017
DOI: 10.1159/000479631
|View full text |Cite
|
Sign up to set email alerts
|

Changing Characteristics of Obese Children and Adolescents Entering Pediatric Lifestyle Intervention Programs in Germany over the Last 11 Years: An Adiposity Patients Registry Multicenter Analysis of 65,453 Children and Adolescents

Abstract: Objective: To examine whether characteristics of children and adolescents who start lifestyle intervention (LI) for obesity in Germany changed over the last decade. Methods: 65,453 subjects (<21 years) from the APV database (Adiposity Patients Registry) with a BMI ≥ 90th percentile were included (years 2005-2015). Logistic regression models (confounders: age, sex, migration background) were created for overweight, obesity, extreme obesity, and obesity-related comorbidities. Comorbidities were further adjusted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
9
0
5
Order By: Relevance
“…The high blood pressure levels observed in the present study in the German cohort were in line with a European health interview survey, which reported higher prevalence of hypertensive diseases in the population aged 15 years and over in Germany (28.5%) than in Norway (12.7%) and Italy (20.6%) . A study published in 2017 also showed a very high frequency of elevated BP in German adolescents with obesity , although using different cut‐off values than this study. Our findings of lowest prevalence of metabolic syndrome in the Norwegian cohort are also in consistence with an international comparison that showed children from Germany in the highest cardiovascular risk tertile, Italy in the middle and children from Norway in the tertile with most favourable cardiovascular risk profile overall .…”
Section: Discussionsupporting
confidence: 45%
“…The high blood pressure levels observed in the present study in the German cohort were in line with a European health interview survey, which reported higher prevalence of hypertensive diseases in the population aged 15 years and over in Germany (28.5%) than in Norway (12.7%) and Italy (20.6%) . A study published in 2017 also showed a very high frequency of elevated BP in German adolescents with obesity , although using different cut‐off values than this study. Our findings of lowest prevalence of metabolic syndrome in the Norwegian cohort are also in consistence with an international comparison that showed children from Germany in the highest cardiovascular risk tertile, Italy in the middle and children from Norway in the tertile with most favourable cardiovascular risk profile overall .…”
Section: Discussionsupporting
confidence: 45%
“…Суть цієї гіпотези полягає в тому, що недостатнє харчування в період внутрішньоутробного розвитку або раннього періо-УДК 616.379-008.64-085-035.2-008. 9 ду життя дитини є однією з основних причин уповільненого розвитку ендокринної функції підшлункової залози і схильності до ЦД 2-го типу. Може здатися сумнівним, що явища, які розвиваються в перші два роки життя дитини, здатні викликати зміни ендокринних функцій до 50-70 років життя.…”
Section: International Journal Of Endocrinologyunclassified
“…На сьогодні ожиріння у світі набуло характеру епідемії, в тому числі і в дитячій популяції. Отже, очікується подальше неухильне зростання числа випадків ЦД 2-го типу [7][8][9].…”
Section: International Journal Of Endocrinologyunclassified
“…Physical activity has been recommended in the prevention of obesity and dyslipidemia by health organizations around the world, because it costs less and generates fewer side effects than isolated medicine (20,23). Most studies on prevention of dyslipidemia adopted the traditional statistical methods and the interaction between demographic characteristics, lifestyle behaviors and dyslipidemia has rarely been incorporated into the research (17,24,25).…”
Section: Introductionmentioning
confidence: 99%